PELATIHAN PENGELOLAAN DIGITAL MARKETING PADA KOMUNITAS SINKAPRENUER DI KOTA SINGKAWANG - Yohanes Gala Araftake Blikololong; Kasnur Saputra; Syska Gloria; Legawa Tegar Ramadhan; Sutarto sutarto (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: Digital marketing is a form of marketing that utilizes digital platforms and internet technology to promote products and services to a wider audience. In the increasingly developing digital era, digital marketing has become an important component in business strategy because it can increase reach, cost efficiency, and effectiveness of marketing campaigns. Digital marketing is an important strategy in facing the development of information technology. Micro, Small, and Medium Enterprises (MSMEs) are required to be able to adapt to the digital era in order to increase competitiveness and expand market reach. This community service activity aims to improve the understanding and skills of MSME actors under the auspices of the Sinkaprenuer community in Singkawang City in terms of digital marketing. The implementation method of this activity includes counseling, training, and direct practice. The results of this activity show an increase in participants' knowledge of digital marketing strategies, as well as the emergence of motivation to utilize digital media in business development. This community service is expected to be a stimulus for other MSME communities in increasing their digital capacity.Â Keywords: MSMEs, digital marketing, training, Sinkaprenuer, Singkawang.